Influence of invasive crayfish on fine sediment transport, ingress and bed storage in lowland rivers. (15th June 2022) - Mathers, Kate L.; Rice, Stephen P.; Chadd, Richard; Wood, Paul J.
Abstract: Historically it has been assumed that abiotic forces dominate fluvial sediment dynamics. However, a growing body of work indicates that biological energy can also exert a significant control over sediment dynamics. The role that invasive species may play in altering fine sediment dynamics is particularly pertinent given that any influence may disrupt the natural equilibrium of the ecosystem. Here we investigated the effect of invasive signal crayfish ( Pacisfastcus leniusculus ) on the transport and storage of fine sediment in a densely populated river compared with a nearby control river without crayfish, over an 18‐week period. We observed clear evidence of diurnal fluctuations in turbidity associated with crayfish presence including periodograms with power peaks at a period of 1 day. Fine sediment fluxes indicated that crayfish contributed on average 18.5% extra to baseflow loads than would be likely under abiotic forcing alone. Temporal variations in suspended sediment concentrations were also observed at the control site but these were different in character and exhibited no clear temporal pattern or consistency as confirmed by periodogram analysis. Crayfish did not have an effect on sediment ingress rates relative to the control site and, at the crayfish site, the reach scale sediment budget was in net equilibrium during the sampling period. Our results provide further evidence that biological energy alters riverine fine sediment dynamics and warrants consideration in sediment dynamic models.